(3GdZQjH GdeUfas - (3GdbGSe Hf SdGe GdgQhj GdCROj GdNRGYj, CHh YHjO, J (B224 (3g` s
(3ChdgG (B:s
(3CNHQfG GdTjN CHh HcQ YHO GdQGRb Hf Ydi Hf GdMSjf GdcQeGfi bGd CHh YHjO hefg GdMOjK GdBNQ (B( (3Cf GdeSLO djfRhi ef GdJNGeI ceG JfRhi GdLdOI ai GdfGQ (B) s
(3BNQgG (B:s
(3hai MOjK BNQ EfeG SeYJg ef eYGP Hf HQg Yf QShd Gddg Udi Gddg Ydjg hSde bhdg (B:( (3jOHQg jYfi jMOKg (B) (3Ke cJGH ZQjH GdMOjK Yf CHj YHjO GdbGSe Hf SdGe s
(3GdfSNI HgG MhGTs
(3Ydjg NW GHf aQM GddNeI GdGTHjdi hYOI SeGYGJ ai GdbQf GdSGOS bhHdJ GdfSNI YOI eQGJs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B176 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B101s
Keywords: (3GdMOjK h GdeUWdMs